Adaptive responses to mTOR gene targeting in hematopoietic stem cells reveal a proliferative mechanism evasive to mTOR inhibition - Fan, Cuiqing (Proc Natl Acad Sci U S A, 2021)
The mechanistic target of rapamycin (mTOR) is a central regulator of cell growth and an attractive anticancer target that integrates diverse signals to control cell proliferation. Previous studies using mTOR inhibitors have shown that mTOR targeting suppresses gene expression and cell proliferation. To date, however, mTOR-targeted therapies in cancer have seen limited efficacy, and one key issue is related to the development of evasive resistance. In this manuscript, through the use of a gene targeting mouse model, we have found that inducible deletion of mTOR in hematopoietic stem cells (HSCs) results in a loss of quiescence and increased proliferation. Adaptive to the mTOR loss, mTOR(−/−) HSCs increase chromatin accessibility and activate global gene expression, contrary to the effects of short-term inhibition by mTOR inhibitors. Mechanistically, such genomic changes are due to a rewiring and adaptive activation of the ERK/MNK/eIF4E signaling pathway that enhances the protein translation of RNA polymerase II, which in turn leads to increased c-Myc gene expression, allowing the HSCs to thrive despite the loss of a functional mTOR pathway. This adaptive mechanism can also be utilized by leukemia cells undergoing long-term mTOR inhibitor treatment to confer resistance to mTOR drug targeting. The resistance can be counteracted by MNK, CDK9, or c-Myc inhibition. These results provide insights into the physiological role of mTOR in mammalian stem cell regulation and implicate a mechanism of evasive resistance in the context of mTOR targeting.